Unpacking the nonlinear effect of self-efficacy in entrepreneurship: why and under which condition more is not better - Uy, Marilyn A. (2023)
Self-efficacy exerts a positive impact on several self-regulatory functions to support goal accomplishment and performance. However, in contexts that are characterized by uncertainty and ambiguity, such as entrepreneurship, there might be a tipping point to this relationship, prompting calls for deeper investigations on the nonlinear effect. In particular, the underlying mechanisms explaining why and when the nonlinear effect occurs are unclear. Drawing on theories of self-regulation, we examine the nonlinear effect of entrepreneurial self-efficacy on venture goal progress through the entrepreneur's active feedback-seeking and venture effort. We also propose that the entrepreneur's state error mastery orientation moderates the nonlinear effect. Conducting a six-wave repeated measures study among 84 early-stage entrepreneurs in a business accelerator in the Philippines, we use a within-person approach to test our hypotheses and research model. Results suggest that self-regulatory mechanisms in terms of feedback seeking, effort, and state error mastery orientation help to unpack why and when self-efficacy exerts a nonlinear effect on performance outcomes.